WELCOMING YOUNG CHILDREN INTO THE MUSEUM : a practical guide. - Erdman, Sarah ([Place of publication not identified] : ROUTLEDGE, 2021)
Welcoming Young Children into the Museum provides all of the information practitioners need to consider when making the decision to engage with this audience and their carers. Meeting the reader where they are, this guide enables professionals to work toward outcomes that fit with their needs. Working methodically from the initial stages of bringing staff on board, through to implementation and evaluation, readers are carefully steered through each phase. "Big-picture" needs, like adherence to mission, are considered alongside logistical components, like cleaning schedules, to ensure that museums cater to young children in a way that is beneficial to both the visitors and the institution. Drawing on current neurological research and best practices in early childhood education and development, this guide presents case studies from a variety of different institutions around the world that demonstrate that creating interesting, developmentally appropriate opportunities for young children is about much more than just simplifying what is already on offer. Erdman, Nguyen and Middleton demonstrate that the age and needs of the visitors must be taken into careful consideration, as well as the assets and potential obstacles of the institution. Welcoming Young Children into the Museum will be essential reading for professionals working in museums large and small, regardless of type. It will be useful to those who are considering setting up new programmes for early years audiences and those with existing programmes, who would like to improve their offering.
Keywords: Museums and children; EDUCATION / General; EDUCATION / Preschool & Kindergarten